Mechanistic Analysis and Numerical Simulation of the 2021 Post‐Fire Debris Flow in Xiangjiao Catchment, China. Issue 1 (24th January 2023) - Ouyang, Chaojun; Xiang, Wen; An, Huicong; Wang, Fulei; Yang, Weibin; Fan, Jiying
Abstract: Wildfires are becoming a global natural disaster under climate change. A worthwhile concern is that the rainfall thresholds that trigger debris flows in catchments affected by recent wildfires are much lower than those that trigger debris flows in catchments with similar environments but that have not experienced wildfires. In this study, we investigated a major post‐fire debris flow event in Xiangjiao catchment triggered by heavy rainfall in 2021. Through the combination of field observation, laboratory experiments and several numerical models (rainfall interception, infiltration, erosion and runoff models), the physical mechanistic analysis and numerical simulation of the post‐fire debris flow in Xiangjiao catchment was carried out. Results show that the simulated deposited area, erosion depth, and the occurrence time of debris‐flow initiation correlate well with the actual situation. It is demonstrated that the numerical simulation method used in this study can be used to effectively describe the characteristics of the initial and propagation stages of the post‐fire debris flow generated by runoff and provide important insights and guidance for the prediction and prevention of debris‐flow disasters in catchments affected by wildfire. Plain Language Summary: Wildfires are becoming more and more common under more frequent extreme weather. After the wildfire, the overall environment would be substantially changed, which will lead to more frequent debris‐flow disasters. Consequences of these changes are worthy to be deeply investigated. In this study, we investigated a major 2021 post‐fire debris flow event in Xiangjiao catchment, China, triggered by heavy rainfall. Through the combination of field observation, laboratory experiments, and numerical models, the physical mechanistic analysis and numerical simulation of the post‐fire debris flow in Xiangjiao catchment was carried out. Key Points: The mechanism of post‐fire debris flows caused by runoff in Xiangjiao catchment is analyzed Using multiple numerical models and multi‐source data, the 2021 Xiangjiao post‐fire debris flow is simulated The numerical simulation results are analyzed and correlated well with the field investigation